1936
DOI: 10.1002/ar.1090650103
|View full text |Cite
|
Sign up to set email alerts
|

Monstrosities produced by the injection of selenium salts into hens' eggs

Abstract: Chick monsters were consistently produced in eggs from localities where low hatchability had been observed and where toxic foodstuffs were produced (Franke and Tully, '35). I n order to prove that the foodstuff, and not the quality of the stock, was the causative factor, chicks of known stock were fed toxic grain produced in the localities where low hatchability and toxic foodstuffs are common (Tully and Franke, '35 ; Franke and Tully, '36). Following the clue provided by Robinson ( '33) who demonstrated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
1

Year Published

1938
1938
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(11 citation statements)
references
References 7 publications
2
8
1
Order By: Relevance
“…This is in contrast to previous studies by Franke et al (1936) and Westfall (1938). These workers found that of the embryos were abnormal when injected with 0.6 and 0.7 ppm of Se, respectively, as sodium selenite preceding incubation.…”
contrasting
confidence: 99%
“…This is in contrast to previous studies by Franke et al (1936) and Westfall (1938). These workers found that of the embryos were abnormal when injected with 0.6 and 0.7 ppm of Se, respectively, as sodium selenite preceding incubation.…”
contrasting
confidence: 99%
“…of selenium as Na 2 Se0 3 into eggs prior to incubation, monstrosities were produced at the end of the hatching period. The bizarre results were similar to those found elsewhere (Franke et al, 1936), and because of this, there is little need to elaborate further. The distribution of Se-75 in newly hatched chicks receiving trace amounts of selenium is shown in Table 1.…”
supporting
confidence: 87%
“…In birds, selenium-caused malformations, such as hydrocephaly, beak defects, microphthalmia, anophthalmia, and foot defects, were observed in duck [2,3] and chicken [4][5][6] embryos when given to hens or injected to eggs. In mammals, however, teratogenicity of Se has not been clearly shown.…”
Section: Introductionmentioning
confidence: 99%